Religious motives in the dastan “Idegey” - Valiullina F.M. (Золотоордынское обозрение)
The purpose of the study: An analysis and systematization of religious motives in the Tatar versions of the epos “Idegey”. Research materials: The main sources are published and archival Tatar versions of the epos “Idegey”, research by famous folklorists, and information from literary and scientific sources. The scientific novelty of the study arises from the fact that an attempt to systematize religious motives in the dastan “Idegey” was based on the study of existing research and a comparative analysis of different options from archival sources. Research results: This work proves that, compared to the mythological layer, the religious layer of the epos is not so rich. In general, even the used and preserved part has an enormous semantic load and artistic and aesthetic value. The work explores motives showing the attitude of Toktamysh Khan, Idegey, and Nuradyn to religion, and images associated with the cult of Islam such as Allah (Alla, Tengri), Ghazazil, angels, gurias, etc. According to the author, unlike religious genres, especially munajats and baits, religious ideology and motives do not occupy a large place in epic works. But they have a certain functional load. Religious motives are not limited to the narration of the people’s attitude of that era to religion; they also contribute to the understanding of religious, philosophical, and moral views while revealing what place religion occupied among the masses of that times.